Intertekstualność Norwida. Przypadek jednego wiersza = Norwid`s intertextuality. One line case - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a proposal to read one poem by Norwid as a text with intermedia values. The author starts with self-referential statements by the poet, undermining the then patterns of the creator-bard, and takes into account the aesthetic theories of the time. In his research, he follows the recognized path of the artist`s natural relationship with the visual arts, as well as with the romantic theory of the correspondence of arts. In this context, I interpret Norwid`s lyrical fragment as an attempt to reference to a tragic event in history - the suicide of the conspirator Karol Levittoux, however, already from a universal perspective.
Keywords: słowo; obraz; historia; korespondencja sztuk; intertekstualizm; word; image; history; correspondence of arts; intertextualism